HAT-P-55b: A Hot Jupiter Transiting a Sun-Like Star*: HAT-P-55b: A Hot Jupiter Transiting a Sun-Like Star. (4th January 2016) - Juncher, D.; Buchhave, L. A.; Hartman, J. D.; Bakos, G. Á.; Bieryla, A.; Kovács, T.; Boisse, I.; Latham, D. W.; Kovács, G.; Bhatti, W.; Csubry, Z.; Penev, K.; et al.
Abstract: We report the discovery of a new transiting extrasolar planet, HAT-P-55b . The planet orbits a V = 13.207 ± 0.039 sun-like star with a mass of 1.013 ± 0.037 M ⊙, a radius of 1.011 ± 0.036 R ⊙, and a metallicity of -0.03 ± 0.08. The planet itself is a typical hot Jupiter with a period of 3.5852467 ± 0.0000064 days, a mass of 0.582 ± 0.056 M J and a radius of 1.182 ± 0.055 R J . This discovery adds to the increasing sample of transiting planets with measured bulk densities, which is needed to put constraints on models of planetary structure and formation theories.